2009
DOI: 10.1159/000267227
|View full text |Cite
|
Sign up to set email alerts
|

Sedation during Flexible Bronchoscopy in Patients with Pre-Existing Respiratory Failure: Midazolam versus Midazolam plus Alfentanil

Abstract: Background: The use of sedation during flexible bronchoscopy (FB) is undisputed; however, the combination of benzodiazepines and opiates, although reasonable, is suggested to cause hypoventilation, particularly in patients with pre-existing respiratory failure. Objectives: To assess respiratory function during FB. Methods: Transcutaneous PCO2 (PtcCO2), oxygen saturation, patients’ tolerance, time after FB until recovery and application of drug dosage were assessed in patients receiving ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 30 publications
3
60
1
Order By: Relevance
“…When used in combination with midazolam, FOX et al [29] found that these patients had adequate sedation and attenuation of sympathetic responses. DREHER et al [48] compared consecutive patients with stable pre-existing respiratory failure undergoing flexible bronchoscopy receiving midazolam alone or midazolam-alfentanil combination. They did not find any differences in oxygen desaturation or hypoventilation but those in the combination group reported less discomfort.…”
Section: Opioidsmentioning
confidence: 99%
“…When used in combination with midazolam, FOX et al [29] found that these patients had adequate sedation and attenuation of sympathetic responses. DREHER et al [48] compared consecutive patients with stable pre-existing respiratory failure undergoing flexible bronchoscopy receiving midazolam alone or midazolam-alfentanil combination. They did not find any differences in oxygen desaturation or hypoventilation but those in the combination group reported less discomfort.…”
Section: Opioidsmentioning
confidence: 99%
“…Over the years, bronchoscopists have used several drugs, alone or in combination, for sedation, but the majority of studies have evaluated benzodiazepines (mainly diazepam and midazolam) and narcotics (mainly opioids, such as fentanyl and alfentanil), or combinations of these [16][17][18][19][20]. The combination of the sedative and amnesic effects of benzodiazepines with the analgesic and the antitussive actions of opioids is able to provide effective conscious sedation [15], and this is probably the most commonly used regimen in bronchoscopy [21], even if there are not many studies that compared the use of a single drug with a combination (and those that did gave controversial results).…”
mentioning
confidence: 99%
“…In general, the amount of anaesthetics or analgesics needed to establish an LMA is less than that required for tracheal intubation. Recent studies have also demonstrated the occurrence of alveolar hypoventilation, as estimated by an increase in the partial pressure of carbon dioxide, during FOB under sedation (21,34). In our procedure, mechanical ventilation is immediately applied to maintain the appropriate minute volume if the sedatives suppress the patient's spontaneous breathing.…”
Section: Discussionmentioning
confidence: 89%